Deadly ever after : a Lighthouse Library mystery - Gates, Eva, 1951- (Gates, Eva, 1951- Lighthouse library mystery., 2021)
"They're getting married! Lucy Richardson and Connor McNeil have announced their engagement. Their friends throw a party but...who should arrive, but Richard Eric Lewiston III, Lucy's former almost-fiancé and his overbearing mother Evangeline. Push comes to love when Evangeline makes no secret of why she's here: to get Lucy and Ricky back together...Evangeline throws a dinner party...for a reluctant Lucy and her family...But when a body is found at the restaurant's kitchen door, Lucy is again forced to unwillingly put on her detective's hat and do what she can to save her family and her engagement"--